2010
DOI: 10.1007/s11581-010-0456-8
|View full text |Cite
|
Sign up to set email alerts
|

Vermiculite as an exchanger for copper(II) and Cr(III) ions, kinetic studies

Abstract: The adsorption of Cu(II) and Cr(III) ions by pure clay mineral, vermiculite, was examined in aqueous solution with respect to the adsorbent dose, initial metal ion concentration, pH, and contact time. The studies showed that vermiculite can be used as an adsorbent material for the moderate removal of Cr(III) and Cu(II) from aqueous solutions. Lagergren first-order, pseudo-second-order, and intraparticle diffusion models were used to describe the kinetic data. The kinetics of adsorption indicates that the proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 26 publications
0
10
0
2
Order By: Relevance
“…The use of vermiculite as an adsorbent has been studied for the removal of Hg(II) (Do Nascimento and Masini, 2014), Cr(III) (Badawy et al, 2010;Sis and Uysal, 2014), Cu(II) (Badawy et al, 2010), Pb(II) (Hongo et al, 2012;Sis and Uysal, 2014), Zn(II) (Sis and Uysal, 2014), Cs (Suzuki et al, 2013), Ag(I) (Sari and Tüzen, 2013), Cr(VI) (Dultz et al, 2012), Cd(II) (Panuccio et al, 2009), mineral and canola oils (Mysore et al, 2005), phthalate (Wen et al, 2013), basic cationic dye (Choi and Cho, 1996), herbicides 2,4-D, diuron, alachlor, metolachlor and triazine (de Rezende et al, 2011), dibenzothiophene (Froehner et al, 2010), benzodiazepine (Carvalho et al, 2014) and cationic surfactant cetylpyridinium chloride (Tarasevich et al, 2013) from aqueous solution. Although there are many works published about the adsorption of metal ions and organic compounds onto vermiculite, only one study has been carried out to determine the dye adsorption properties of vermiculite.…”
Section: Introductionmentioning
confidence: 99%
“…The use of vermiculite as an adsorbent has been studied for the removal of Hg(II) (Do Nascimento and Masini, 2014), Cr(III) (Badawy et al, 2010;Sis and Uysal, 2014), Cu(II) (Badawy et al, 2010), Pb(II) (Hongo et al, 2012;Sis and Uysal, 2014), Zn(II) (Sis and Uysal, 2014), Cs (Suzuki et al, 2013), Ag(I) (Sari and Tüzen, 2013), Cr(VI) (Dultz et al, 2012), Cd(II) (Panuccio et al, 2009), mineral and canola oils (Mysore et al, 2005), phthalate (Wen et al, 2013), basic cationic dye (Choi and Cho, 1996), herbicides 2,4-D, diuron, alachlor, metolachlor and triazine (de Rezende et al, 2011), dibenzothiophene (Froehner et al, 2010), benzodiazepine (Carvalho et al, 2014) and cationic surfactant cetylpyridinium chloride (Tarasevich et al, 2013) from aqueous solution. Although there are many works published about the adsorption of metal ions and organic compounds onto vermiculite, only one study has been carried out to determine the dye adsorption properties of vermiculite.…”
Section: Introductionmentioning
confidence: 99%
“…The most widely employed adsorbent is activated carbon due to its pore structure, high efficiency, and adsorption capacity for some dyes, but the cost and difficulty in separation after adsorption hinder its large-scale application [5]. Several low-cost adsorbents such as vermiculite [6], hazelnut shell [7], and rice husk ash [8] have also been investigated for decontamination purpose; however, the adsorption capacities of these adsorbents were restricted. Therefore, many researchers have taken up with seeking for more effective adsorbents to eliminate these hazardous dyes from the effluent from the viewpoints of environment and scientific and technological importance.…”
Section: Introductionmentioning
confidence: 99%
“…The increase of t pH results in an increase of the hydroxyl groups and other anionic functional groups. This makes the bacterial surface more negative, the number of electrostatic repulsions decreases and the number of electrostatic attraction increases, resulting in an increase of metal sorption (Badawy et al, 2010).…”
Section: Effect Of Metal On the Microbial Growthmentioning
confidence: 99%
“…Vermiculite can adsorb heavy metals by two distinct mechanisms: production of inner-sphere complexes through SieO À and AleO À groups at the vermiculite particle edges and cation exchange at the planar site. Since both mechanisms are pH-dependent and pH changes the vermiculite surface properties and the metal speciation, it is concluded that pH plays an important and crucial role in the control of cationic adsorption from aqueous solutions (Badawy et al, 2010).…”
Section: Nickel Sorption By Vermiculite E Process Modellingmentioning
confidence: 99%